2017
DOI: 10.1038/tp.2016.265
|View full text |Cite
|
Sign up to set email alerts
|

Default mode network deactivation during emotion processing predicts early antidepressant response

Abstract: Several previous functional magnetic resonance imaging (fMRI) studies have demonstrated the predictive value of brain activity during emotion processing for antidepressant response, with a focus on clinical outcome after 6–8 weeks. However, longitudinal studies emphasize the paramount importance of early symptom improvement for the course of disease in major depressive disorder (MDD). We therefore aimed to assess whether neural activity during the emotion discrimination task (EDT) predicts early antidepressant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 88 publications
5
28
0
Order By: Relevance
“…Elevated pretreatment anterior cingulate activity is most often reported in resting state or facial emotion tasks [6]. Furthermore, the time points of measurement might impact results, since early response might underlie a different neuronal activity as late response [42,43]. A sigmoid response indicates that individual patients respond with a moderate decline of HAM-D values in the beginning, followed by at a certain period of faster response and an again flatter decline at the end of observations.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated pretreatment anterior cingulate activity is most often reported in resting state or facial emotion tasks [6]. Furthermore, the time points of measurement might impact results, since early response might underlie a different neuronal activity as late response [42,43]. A sigmoid response indicates that individual patients respond with a moderate decline of HAM-D values in the beginning, followed by at a certain period of faster response and an again flatter decline at the end of observations.…”
Section: Discussionmentioning
confidence: 99%
“…The same correspondence between connectivity, neurochemistry and cognition applies to the relation between DMN and emotional modulation (Alcalá-López et al, 2017;Bzdok et al, 2013;Mars et al, 2012;Raichle, 2015;Spies et al, 2017;Zhao et al, 2017). The nucleus accumbens is a central output for the dopaminergic projections and is involved in emotion regulation and affect integration (Floresco, 2015;Laviolette, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, as a key hub within the default mode network (DMN) (29), rACC abnormalities – such as manifested in reduced volume – may contribute to maladaptive forms of self-referential processing (24), which could interfere with successful engagement in depression treatment. Of relevance – although not specifically focused on the rACC – a recent study found that greater deactivation of the DMN while engaging with an emotional task predicted enhanced antidepressant response (65). …”
Section: Discussionmentioning
confidence: 99%